Salient Depositional Structures from Bombay Volcanic Complex, Western Deccan Volcanic Province, Deccan Flood Basalt, India - R. K. Sharma (Salient Depositional Structures from Bombay Volcanic Complex, Western Deccan Volcanic Province, Deccan Flood Basalt, India, 2022)
The LIP’s of the world have probably the largest published literature on them including Deccan Flood basalt but still the aspect of tectono-magmatic environment of emplacement of the hybrid type of rocks of the Bombay Volcanic complex remains wide open till date. Here in this short write up author has tried to report some very salient depositional structures from the volcaniclastic deposits and associated basaltic flows from the area north of Bombay (Mumbai), which is designated as Bombay volcanic complex and has been dubbed as youngest unit of the DVFB in Western Deccan Province. These structures and micro textures of the ejecta from this area have been explained and interpretations have been made to indicate and infer possible mechanism of emplacement of these volcanic rocks.